Factors That Affect User Satisfaction Of Electronic Learning Management Systems (ELMSs) - Riyadi, Riyadi; Nimran, Umar; Sukoharsono, Eko Ganis; Musadieq, Muhammad Al (JPAS (Journal of Public Administration Studies), 2020)
This research intends to explore a variety of factors that may affect the satisfaction use of ELMSs. Therefore, various factors have been tested empirically by using another model approach integrated into a single model. Other variables that are still reliable for further research without changing the construct of the indicators are subjective norms, usability, perceived innovation and satisfaction. Some relationships between variables that have significant influence include usability on perceived innovation, perceived innovation on satisfaction. One relationships between variables that have a small influence subjective norms on perceived innovation.